Underlying lending loans principle based on 7 C’s of credit assessment in credit processing department: a case study of Bank Kerjasama Rakyat (M) Berhad Malacca Branch / Muhammad Syafiq Anuar - Anuar, Muhammad Syafiq (Faculty of Business and Management, 2011)
The “7 C’s of credit” or "7C's of banking" are a common reference to the major elements of a banker’s analysis when considering a request for a loan. Namely, these are Cash Flow, Collateral, Capital, Character, Conditions Common sense and Compliance. This study will provide an in-depth description of each of the 7 C’s of credit or banking and the implementation of this 7C’s in credit assessment approach in credit processing at Bank Kerjasama Rakyat (M) Berhad, Malacca Branch to evaluating credit risk associated with the loan proposals and approval where there is important to help lenders understand what banker needs to understand about your business in order to approve their loan. This study also to recognize whether BKRM using 7C’s during loan appeal and practice concept of the 7C’s credit approach used to measure the credit worthiness of the borrowers. To study the subject matter even further, the researcher had used two approaches in gathering the data and views which are through the primary data and secondary data. The researcher had interviewed the head of credit units from the Bank Kerjasama Rakyat (M) Berhad, Malacca Branch to examine whether he make an approval for customers loan based on this 7C’s credit assessment or not. Besides that, the researcher also does some observation to get more details and further information on this case study. To make this study more specific, precise and relevant researcher also used the secondary data for this study. The researcher had gathered the views and data from previously published case studies and researches. The results obtained were revealing that the Bank Kerjasama Rakyat (M) Berhad, Malacca Branch implements all the 7C’s of credit assessment approach in determining the credit worthiness of the borrowers. Besides that, the bank used other than these 7C’s of credit approach which are competition approach and credit structure approach in order to grant credit to the borrowers. Hopefully this study has succeeded in helping you understand where your banker is coming from will have insight as to where your banker is coming from, and therefore better prepare you to handle their questions and concerns. The bank must operate well defined credit granting criteria in order to get a better credit granting process, which includes a clear indication of the bank’s target market and a thorough understanding of the borrower as well as the purpose and structure of the credit, and its source of repayments.